Aberrant immune response with consequent vascular and connective tissue remodeling – causal to scleroderma and associated syndromes such as Raynaud phenomenon and other fibrosing syndromes?. Issue 6 (November 2016) - Durmus, Nedim; Park, Sung-Hyun; Reibman, Joan; Grunig, Gabriele
Abstract : Purpose of review: Scleroderma and other autoimmune-induced connective tissue diseases are characterized by dysfunctions in the immune system, connective tissue and the vasculature. We are focusing on systemic sclerosis (SSc)-associated pulmonary hypertension, which remains a leading cause of death with only a 50–60% of 2-year survival rate. Recent findings: Much research and translational efforts have been directed at understanding the immune response that causes SSc and the networked interactions with the connective tissue and the vasculature. One of the unexpected findings was that in some cases the pathogenic immune response in SSc resembles the immune response to helminth parasites. During coevolution, means of communication were developed which protect the host from over-colonization with parasites and which protect the parasite from excessive host responses. One explanation for the geographically clustered occurrence of SSc is that environmental exposures combined with genetic predisposition turn on triggers of molecular and cellular modules that were once initiated by parasites. Summary: Future research is needed to further understand the parasite-derived signals that dampen the host response. Therapeutic helminth infection or treatment with parasite-derived response modifiers could be promising new management tools for autoimmune connective tissue diseases.